Covid-19 in pregnant women and babies: What pediatricians need to know (2020)
Beginning in late 2019, a novel coronavirus labeled SARS-CoV-2 spread around the world, affecting millions. The impact of the disease on patients and on health care delivery has been unprecedented. Here, we review what is currently known about the effects of the virus and its clinical condition, Covid-19 in areas of relevance to those providing care to neonates. While aspects of pregnancy, including higher expression of the cell receptor for the virus, ACE2, could put these women at higher risk, preliminary epidemiological information does not support this. Viral carriage prevalence based on universal screening show that rates vary from 13% in “hot spots” such as New York City, to 3% in areas with lower cases. Vertical transmission risks are unknown but 3.1% of 311 babies born to mothers with Covid-19 were positive within a week of birth. The clinical description of 26 neonates <30 days of age showed no deaths and only one requiring intensive care. Risks for breast-feeding and for milk banks are discussed.